2015
DOI: 10.1124/mol.114.097436
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effects of Ingenol 3,20-Dibenzoate on the Erythropoietin Receptor: Synergism at Low Doses and Antagonism at High Doses

Abstract: Although ingenol 3,20-dibenzoate (IDB) is known as a selective novel protein kinase C (PKC) agonist, its biologic actions and underlying mechanisms remain incompletely understood. In this study, we identified IDB as a proliferative agent for an erythropoietin (EPO)-dependent cell line, UT-7/EPO, through the screening of a natural compound library. To clarify the underlying mechanism of IDB's EPO-like activities, we thoroughly analyzed the mutual relation between EPO and IDB in terms of in vitro and in vivo act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our study has some limitations. Given the technical challenges associated with measuring PKC modulator pharmacokinetics in vivo 27 , more work is needed to determine in vitro doses of these compounds that reflect efficacious clinically-achievable exposures, particularly as phenotypic and functional outcomes may be highly dose-dependent 36 54 55 . The increased expression of CD25 on T cells after an oral dose of Vorinostat but not following exposure to the drug in vitro suggests that LRAs may have effects on T cell tissue distribution that could not be measured in a static in vitro system.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has some limitations. Given the technical challenges associated with measuring PKC modulator pharmacokinetics in vivo 27 , more work is needed to determine in vitro doses of these compounds that reflect efficacious clinically-achievable exposures, particularly as phenotypic and functional outcomes may be highly dose-dependent 36 54 55 . The increased expression of CD25 on T cells after an oral dose of Vorinostat but not following exposure to the drug in vitro suggests that LRAs may have effects on T cell tissue distribution that could not be measured in a static in vitro system.…”
Section: Discussionmentioning
confidence: 99%
“…IDB exhibits various biological activities, including anti-inflammatory and anticancer effects 18 , 19 ; therefore, further understanding of the precise mechanism of action of IDB is crucial for its potential therapeutic applications. Despite ongoing research and numerous studies, the precise mechanism of action of IDB is yet to be fully elucidated 20 , 21 . We found that 6.7% (32 out of 480) of the significant genes exhibited IDB-specific effects (Fig.…”
Section: Resultsmentioning
confidence: 99%